EMPOWERMENT AND EXPLOITATION: ANALYSING THE ROLE OF WOMEN WORKERS IN BANGLADESH'S READY-MADE GARMENT SECTOR IN DEPZ. - Amin, Dr. Md. Ruhul (Farabi Journal of Social Sciences, 2026)
Purpose. This study investigates the dual dimensions of empowerment and exploitation experienced by women workers in Bangladesh’s Ready-Made Garment (RMG) sector, with a specific focus on the Dhaka Export Processing Zone (DEPZ). It aims to analyse how employment in the RMG industry simultaneously contributes to women’s socio-economic advancement and exposes them to structural vulnerabilities. Design/methodology/approach. A mixed-methods research design was employed, integrating quantitative analysis of industry statistics with qualitative data obtained from semi-structured interviews and focus group discussions with women workers in DEPZ. This approach enabled a comprehensive assessment of employment trends, working conditions, and gendered labour experiences within the RMG sector. Findings. The findings indicate that participation in the RMG sector has enhanced women’s financial independence and social mobility; however, it is also associated with persistent exploitative practices, including low wages, excessive working hours, restricted labour rights, and health-related risks. The study further reveals a declining trend in female participation in the garment industry, suggesting emerging structural and institutional barriers that undermine sustainable women’s employment in the sector. Originality. This research offers an integrated perspective on empowerment and exploitation by empirically linking women’s labour experiences with institutional and policy constraints in export-oriented industrial zones. It contributes to the literature on gender, labour, and industrial development by providing evidence-based insights that inform policy reforms aimed at improving labour rights, working conditions, and gender equity in developing economies. Key words: Women Workers, Ready-Made Garment (RMG) Sector, Dhaka Export Processing Zone (DEPZ), Economic Empowerment, Workplace Exploitation.